AI in Manufacturing and Processing: Shaping the Factories of the Future - Kabeer, Muhammad Mohsin (BULLET : Jurnal Multidisiplin Ilmu, 2022)
This is a review of Artificial Intelligence (AI) and its impact in manufacturing and processing sectors. It emphasizes the fact that AI is to be integrated with Industry 4.0 technologies processes, i.e., the IoT, big data, edge computing, and cyber-physical systems that will allow monitoring in real-time, predictive maintenance, intelligent automation, and process optimization. The most important ones are the enhanced level of productivity, quality of goods, efficiency in terms of costs and better decision-making skills. Poor quality of data, high cost of implementation, employee resistance, and cybersecurity are some of the challenges of AI implementation in spite of its superiority. Future trends are also reviewed and they include explainable AI, human-AI collaboration, sustainable manufacturing, evaluation of federated learning and the presence of digital twins. With further development of AI, its ability to develop more intelligent, adaptive and environmentally friendly industrial systems is huge. Given that current main obstacles to the successful implementation of AI can be addressed by conducting research, innovating, and making important investments, it will lead to the next step of the industrial revolution.